229k views
3 votes
(2n + 4) + 6 = –9 + 4(2n + 1)

User Hallleron
by
5.3k points

2 Answers

5 votes
n = 2.5

2n + 10 = -9 + 8n + 4
2n + 10 = -5 + 8n
15 = 6n
n = 15/6
User Atlasologist
by
5.3k points
7 votes

Answer:

n=2.5

Explanation:

(2n+4)+6=-9+4(2n+1)

Expand parentheses:

2n+10=-9+8n+4

Combine like terms:

15=6n

Divide both sides by 6:

n=2.5

Hope this helps!

User XenoPuTtSs
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.